Are religious believers irrational: a direct test from an efficient market hypothesis - Senarathne, Chamil W. (Czy ludzie religijni są irracjonalni: bezpośredni test z efektywnej hipotezy rynkowej, 2020)
The current literature does not offer a quantitative test of the irrational behaviour of people, especially taking a proxy for irrationality with reference to an economic activity. This paper examines the role of religious believers in carrying out economic activities. The form of stock market efficiency has been taken as a proxy for testing the null hypothesis that religious believers are irrational on average. The findings suggest that equity markets in religious countries are inefficient at ‘weak form’ level. This provides prima facie evidence for the hypothesis that religious believers are irrational on average. As such, the equity price changes of these stock markets can be forecast on the basis of past patterns. Poor income level and education are the main causes for developing irrationality. As these irrationalities cost economies, the policymakers should design and implement more robust policies and guidelines for poverty alleviation and the enrichment of education at country level
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 1, s. 35-53
Keywords: religion; believers; efficient market hypothesis; EMH; atheists; irrationality; education; religia; wierzący; skuteczna hipoteza rynkowa; ateiści; irracjonalność; edukacja